2010
DOI: 10.1371/journal.pcbi.1000980
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Analysis of Neck Linker Extension in Kinesin Molecular Motors

Abstract: Kinesin stepping is thought to involve both concerted conformational changes and diffusive movement, but the relative roles played by these two processes are not clear. The neck linker docking model is widely accepted in the field, but the remainder of the step – diffusion of the tethered head to the next binding site – is often assumed to occur rapidly with little mechanical resistance. Here, we investigate the effect of tethering by the neck linker on the diffusive movement of the kinesin head, and focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 44 publications
3
51
1
Order By: Relevance
“…19,25,26 For a set of particular Kinesin-1 and Kinesin-2 constructs, it was found that processivity decreases with increasing neck-linker length, while shortening of the native neck linker by one amino acid for that motor abolishes processivity. 24,[27][28][29] A continuation of this work showed similar effects for Kinesin-1/ Kinesin-2/Kinesin-3 and Kinesin-7 constructs. 25 In another study, 26 the insertion of up to 26 prolines in the neck linker of human Kinesin-1 was reported to not only slightly decrease run length under lowionic-strength conditions but also strongly decrease motor speed and stall force.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…19,25,26 For a set of particular Kinesin-1 and Kinesin-2 constructs, it was found that processivity decreases with increasing neck-linker length, while shortening of the native neck linker by one amino acid for that motor abolishes processivity. 24,[27][28][29] A continuation of this work showed similar effects for Kinesin-1/ Kinesin-2/Kinesin-3 and Kinesin-7 constructs. 25 In another study, 26 the insertion of up to 26 prolines in the neck linker of human Kinesin-1 was reported to not only slightly decrease run length under lowionic-strength conditions but also strongly decrease motor speed and stall force.…”
Section: Introductionsupporting
confidence: 64%
“…22,23 When modeled as a simple flexible polymer, the tension in the neck linker at a given end-to-end distance and, therefore, the strength of the head-head communication would scale inversely with contour length, that is, number of amino acids. 24 Data from three recent studies support such a simple general model of head-head communication. 19,25,26 For a set of particular Kinesin-1 and Kinesin-2 constructs, it was found that processivity decreases with increasing neck-linker length, while shortening of the native neck linker by one amino acid for that motor abolishes processivity.…”
Section: Introductionmentioning
confidence: 83%
“…The role of the neck linker domain in tethered diffusion of the free head was recently investigated by our group using Brownian dynamics simulations (39). If the neck linker is modeled as a worm-like chain, the neck linker is expected to strongly hinder the diffusion of the tethered head to the next binding site, and a large force between the heads (>30 pN) is expected in the two-head bound state.…”
Section: Resultsmentioning
confidence: 99%
“…The elastic properties of a linker structure in typical molecular motors, like kinesins, have been formerly addressed in experimental studies and molecular dynamics simulations using g rom acs software [68,69], Based on accumulated evidence, it is unlikely that a molecular machine would respond instantaneously to an elongation with an elastic counteraction that resets the linker structure to its equilibrium conformation of length a or shorter (see Fig. 2).…”
Section: A Response To Bursting Fluctuationsmentioning
confidence: 99%